Association of self‐reported financial burden with quality of life and oncologic outcomes in head and neck cancer. Issue 2 (18th November 2021) - Lenze, Nicholas R.; Bensen, Jeannette T.; Farnan, Laura; Sheth, Siddharth; Zevallos, Jose P.; Yarbrough, Wendell G.; Zanation, Adam M.
Abstract: Background: There is a paucity of data on financial toxicity among patients with head and neck squamous cell carcinoma (HNSCC). Materials: This was a retrospective, cross‐sectional study of patients with HNSCC surveyed at an outpatient oncology clinic. Results: The sample included 202 patients with HNSCC with a mean age of 59.6 years (SD 10.0). There were 53 patients (26%) with self‐reported financial burden. Education of high school or less was a significant predictor of self‐reported financial burden (OR 2.52, 95% CI 1.03–6.14, p = 0.042). Patients reporting financial burden had significantly worse physical ( p = 0.003), mental ( p = 0.003), and functional ( p = 0.036) health‐related quality of life (HRQOL). Patients reporting financial burden appeared to have lower 5‐year overall survival (74.3% vs. 83.9%, p = 0.165), but this association did not reach statistical significance. Conclusion: Financial burden or toxicity may affect approximately a quarter of patients with HNSCC and appears to be associated with worse HRQOL outcomes.